A Study of Institutional, Financial, and Regulatory Frameworks of Urban Transport in Large Sub-Saharan African Cities - Adam Smith International (World Bank, Washington, DC, 2014)
This working paper presents the findings of "A Study of Urban Transport Institutional, Financial and Regulatory Frameworks in Large Sub-Saharan African Cites" and it was commissioned by the Sub-Saharan Africa Transport Policy Program (SSATP). The study objective was to review the institutional, financial and regulatory frameworks for the provision of urban transport in four selected cities, Dakar (Senegal), Douala (Cameroon), Kampala (Uganda) and Nairobi (Kenya). The specific focus was to examine: (a) the structure, process and performance of the existing institutions and financing arrangements; and (b) operational practices of public and private bus operators. The study has examined the existing institutional arrangements in the four cities and identified opportunities and constraints for policy reform. The general focus is on identifying mechanisms suitable in different cultural and political environment to organize planning, regulation and monitoring of urban transport services. The study has identified a phased program of improvements required in the urban transport systems, with the short-term measures focused on traffic management, overloading controls, vehicle inspections; medium-term measures focused on a gradual consolidation of the informal sector bus operators into small or medium-sized enterprises, introduction of a formal route structure and licensing system and long-term measures focused on institutional restructuring supported by appropriate legislation, funding and technical support.